Studies on micronutrient cations in arid irrigated aonla orchard soil profiles in Sikar district of Rajasthan (Indian Journal of Arid Horticulture, 2025)
The present study on distribution of micronutrient cataions in arid irrigated aonla orchard soil profiles in Sikar district of Rajasthan was conducted during March 2007-2008. The study included analysis of soil profiles with respect to micronutrients. The available iron ranged between 2.28 to 6.51 mg kg', available zinc between 0.203 to 0.990 mg kg'', available copper between 0.110 to 0.493 mg kg and available manganese between 1.36 to 5.19 mg kg'. All the micronutrients were found to be low to medium in range in arid irrigated aon la orchard soil profiles in Sikar district of Rajasthan.
Keywords: Aonla; Orchards; Micronutrients